The effects of interval training on peripheral brain derived neurotrophic factor (BDNF) in young adults: a systematic review and meta-analysis - García-Suárez, Patricia Concepción (Sci Rep, 2021)
The aim of the current meta-analysis was to determine the effects of acute and chronic interval training (IT) on serum and plasma BDNF concentrations in healthy young adults. A literature search was performed using six databases until February 2020. The TESTEX scale was used to assess the quality of studies. Effect sizes (ES) were computed and two-tailed α values < 0.05 and non-overlapping 95% confidence intervals (95% CI) were considered statistically significant. Heterogeneity, inconsistency (I(2)), and small-study effects using the Luis Furuya–Kanamori (LFK) index were examined. Fifteen studies (n = 277 participants, age = 24 ± 3 years) were included. The overall effects of IT on circulating BDNF concentrations were moderate and significant (ES = 0.62, 95% CI 0.00, 1.24, heterogeneous (p < 0.001), highly inconsistent (I(2) = 90%), and with major asymmetry (LFK index = 2.76). The acute effect of IT on peripheral BDNF levels was large and significant (ES = 1.10, 95% CI 0.07, 2.14), heterogeneous (p < 0.001), highly inconsistent (I(2) = 92%), and with major asymmetry (LFK index = 3.34). The chronic effect of IT on circulating BDNF was large and significant (ES = 0.93, 95% CI 0.40, 1.46), heterogeneous (p < 0.001), with moderate inconsistency (I(2) = 70%), and minor asymmetry (LFK index = 1.21). Acute and chronic IT elicited a moderate increase in serum and plasma BDNF concentrations in a healthy young population.